Pengaruh Cash Turnover terhadap Return on Assets Pada PT Unilever Indonesia Tbk - Reivaldo Reivaldo; Ruhadi Ruhadi; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2022)
The aims of this research to analyze the effect of Cash Turnover (CTO) on Return on Assets (ROA) at PT. Unilever Indonesia for the period 2012-2019. The data that used in this research is the financial statements of PT. Unilever Indonesia During the 2012-2019 Period. The analysis used to determine the effect of Cash Turnover (CTO) on Return On Assets (ROA) is a verification analysis using SPSS 23.0 software. The results of this research indicate that the Cash Turnover (CTO) variable significantly influences Return on Assets (ROA).